Hydropower Development Perspectives in the Context of Climate Change and Environmental Protection (Analele Universității București.Geografie, 2025)
Climate change, the effects of which are already visible, could cause profound damage to the environment in the coming decades. In order to limit global warming to below 2°C above pre-industrial levels, human society must drastically reduce greenhouse gas emissions and make energy consumption more efficient. Although the share of renewable energy sources has increased in recent years, fossil fuels are still widely used. Given the very possible increase in energy demand, the transition to green energy will be a major challenge. Currently, among renewable energy sources, hydropower has the largest contribution to electricity production. Although it is a renewable source, hydropower is not entirely environmentally friendly. Because of this and not only, in the future a massive increase of the other renewable sources (solar, wind, etc.) is foreseen and desired. Based on specific analytical research, this study examines the current state of hydropower and development prospects in the context of climate change and risks to the environment and human health. The future development of hydropower will depend quite a lot on a number of economic, social or environmental factors. Thus, the contribution of hydropower to achieving the objectives of the Paris Agreement is uncertain. Due to its flexibility, hydropower is necessary for the global energy system and must be developed with a minimization of the impact on the environment.